2005
DOI: 10.1002/aic.10391
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization by oscillatory and conventional mixing at constant power density

Abstract: The influence of mixing on crystallization processes has long been recognized. 1,2 The significance of mixing in crystallization is attributed to its role in the development and distribution of supersaturation, as well as the shear forces associated with the velocity field imposed by the impeller motion. These aspects of mixing are paramount to the quality of the precipitates (particles), often characterized by their crystal size distribution (CSD), surface characteristics, chemical purity, and crystalline imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 15 publications
0
17
0
Order By: Relevance
“…6,7 OFRs have been proved to result into significant enhancement in processes such as mass transfer, 8 particle mixing, and separation. 9 The basic concept of an OFR is the application of periodic fluid oscillations to a cylindrical column containing evenly spaced orifice baffles.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 OFRs have been proved to result into significant enhancement in processes such as mass transfer, 8 particle mixing, and separation. 9 The basic concept of an OFR is the application of periodic fluid oscillations to a cylindrical column containing evenly spaced orifice baffles.…”
Section: Introductionmentioning
confidence: 99%
“…Various crystal systems have been investigated in batch OBC platforms including paracetamol, 86,207,208 LGA 209-211 and sodium chlorate. 101,212,213 These studies (largely cooling crystallization) have included the effects of strain and shear on crystal suspensions and it is evident that the hydrodynamic environment of oscillatory mixing offers significant advantages, see Figure 15.…”
Section: Examples Of Crystallization In Ofr Platformsmentioning
confidence: 99%
“…15,16 Crystal product quality can be particularly sensitive to the shear rate distribution during crystallisation. 17,18 Chew et al, 18 investigated the shear rate distribution and flow patterns in a stirred tank and in a moving baffle oscillatory crystalliser (MBOC) using computational fluid dynamics (CFD). They showed that in an MBOC, particles spend most of their time in the high shear regions whilst in the STC/MSMPR particles reside mainly in regions of low shear.…”
Section: Introductionmentioning
confidence: 99%